INEVITABILITY OF ECONOMICALLY INDUCED SEX WORK IN NIGERIA: A MARXIAN POLITICAL ECONOMY APPROACH - Ikezue, Clement Emeka (Practicum Psychologia, 2019)
Commercial sex work is arguably one of the oldest professions on the planet. So many people are involved in the trade either passively or actively. The trade appears to have taken a new dimension with some form of sophistication. The inevitability of economically induced sex work is apparent and disturbing. This paper tried to examine why commercial sex work has persisted in the society even when people paint a sanctimonious posture of themselves. This is against the background that even in the face of seemingly clampdown by the law enforcement agents, the workers appear undeterred. The paper adopted the Marxian Political Economy Approach in explaining the persistence of commercial sex work in Nigeria. Qualitative method of data collection was used in the study. This involved the use of the In Depth Interview (IDI) as instrument for data collection. Collated data were analyzed using the thematic method of qualitative data analysis. It was found in the study that several factors were responsible for the persistence of the economically induced sex work in Nigeria. Prominent among them is the necessity to survive the non friendly economic reality in the country. Lack of empowerment of the female persons in many communities also account for the perpetuity of the trade. The paper recommended among others the empowerment of the female persons in the country with a view to mitigating the non friendly economic reality they face.